Project Management Practices and Challenges in Junior IT Companies - Caldeira, Jéssica Nayara Fernandes; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
Facing the challenges encountered by Information Technology (IT) junior enterprises in software development, this study provides a comprehensive analysis aimed at improving project management. The research seeks to identify the profile and characteristics of junior enterprises, investigate practices and challenges in project clustering, analyze project management processes, and identify risks in project development. Using interviews, literature review, and data analysis, the study offers an in-depth understanding of the environment within these organizations. Expected outcomes include specific proposals to enhance project management, contributing to the knowledge of the sector and providing practical guidelines for junior enterprises and software development startups. This innovative study addresses the gap in research on software management processes for IT junior enterprises, aiming to offer valuable and applicable insights with the potential to positively impact the performance and effectiveness of these organizations.